Procedimentos Técnicos na Iniciação ao Violino: uma sistematização de exercícios de apoio ao repertório Suzuki - Aureliano Afonso Araujo (2007)
The Suzuki method for violin has been largely used as a teaching method for beginners in Brazil. The use of the method, however, is often restricted to the repertoire of the books, not taking into consideration its philosophy and is also done in a traditional way. This thesis analyzes common technical problems that the students might have while dealing with the method and aims to find solutions for them, suggesting preparatory exercises for the repertoire as they are presented in the first three books. These exercises fit in a number of precepts that we call Flesch-Rostal-Bosisio tradition. This tradition is a chain of thoughts that has been evolving through the work of these three great masters. The accuracy of this chain is well know through the results obtained by Professor Pablo Bosisio, who is a national reference regarding the teaching of the violin in Brazil.